Corrosion-driven outward migration and growth of helium bubbles in a nickel-based alloy in high-temperature molten salt environment. (June 2019) - Lei, Guanhong; Yang, Sida; Huang, Hefei; Huang, Qing; Liu, Renduo; Zhang, Wei; Yu, Guojun; Yan, Long
Highlights: A unique outward migration and significant growth of HT-bubbles was observed. Corrosion rather than high-temperature annealing effect is responsible for the behavior of HT-bubbles. The outward migration of HT-bubbles is related to vacancies deficit and slow growth rate of HT-bubbles. Abstract: High-temperature helium ion irradiation was conducted on a nickel-based alloy at 650 °C. A unique outward migration of helium bubbles was observed in the irradiated alloy under molten salt environment, distinguished from the evolution of helium bubbles induced by room-temperature irradiation, which is related to the deficit of vacancies in the high-temperature irradiated alloy and slow growth rate of the bubbles. Moreover, it was elucidated that corrosion induced vacancies rather than high-temperature annealing effect of molten salt is responsible for the evolution of helium bubbles formed by high-temperature helium ion irradiation.